The use of blockchain technology and its reflection in the financial performance of investment projects developed by the Ministry of Sports - Sobhi Noureldin Ata; Ahmed K. Hassan; Hossam S. Selim; Badry E. Hammad; Hussien M. Abdelhalim; Abeer M. Abdelhalim (Economies, 2023)
Blockchain has received a lot of attention in financial technology, as it combines many computer technologies, including data storage, point-to-point transmission, and consensus mechanisms, as it is considered a decentralized technology for managing transactions and data that has been developed. The study aimed to demonstrate the impact of the use of blockchain technology on the financial performance of investment projects developed by the Ministry of Sports. We used the descriptive approach (survey study method) as an appropriate method to achieve the objectives of the study due to the suitability of its procedures. The participants in the study included some leaders of the Ministry of Sports and experts in the field of sports investment, as well as some leaders working in the directorates of youth and sports, and some members of the board of directors of the Olympic Committee, sports federations, sports clubs, and youth centers. The study sample was selected in a deliberate way based on the categories of the study population. There were 300 participants in the study, and the researchers used two questionnaires as tools to collect the data. The results revealed a lack of the use of blockchain technology at the Ministry of Sports and a low level of financial performance at the Ministry of Sports. With a correlation between the level of financial performance and the use of blockchain technology, the level of the financial performance of the investment projects developed by the Ministry of Sports could be predicted based on the use of blockchain technology. Finally, the study also provides insight into political implications, limitations, and future directions.
Keywords: 330; technology; blockchain; financial performance; investment projects; smart contracts